Efficient synthesis of α-galactosylceramide and its C-6 modified analogs - Li, Huiting; Mao, Hongzhao; Chen, Chao; Xu, Ying; Meng, Shuai; Sun, Tiantian; Zong, Chengli (Frontiers in Chemistry, 2022)
The synthesis of α-galactosylceramide (KRN7000) and its C-6 modified analogs remains a challenge due to the difficult α-1,2-cis-glycosidic bond. A non-participating benzyl (Bn) protecting group has been commonly used to favor the α-glycosylation product. Here, we report the α-selective glycosylation by using a bulky 4,6-O-di-tert-butylsilylene (DTBS) galactosyl donor, regardless of the 2-benzoyl (Bz) participating group. Compared with Bn, Bz groups can be selectively removed in basic conditions without impacting the C-6 azide modification. The azide has the potential for clicking with alkyne or being easily transformed to other functional groups.